ロケット コウド ニオケル > 40keV オーロラ デンシ ノ ピッチカク ブンプ a. ニュウシャ リュウシ ト オーロラ ダイ2カイ キョクイキ ニオケル デンリケン ジキケン ソウゴウ カンソク シンポジウム PART 1 - 小玉, 正弘; コダマ, マサヒロ; 奥谷, 晶子; オクタニ, ショウコ; 和田, 雅美; ワダ, マサミ; 今井, 喬; イマイ, タカシ; 竹内, 一; タケウチ, ハジメ; KODAMA, Masahiro; OKUTANI, Shoko; et al. (1980)
P(論文) オーロラ出現中に昭和基地から打ち上げられたS-210JA-20,-21,S-310JA-2の3機のロケット観測により,>40keV電子のピッチ角分布とエネルギーおよび高度との関係を調べた.その結果,ピッチ角分布はどちらにも依存して変化することが分かったが,これは静穏時や北半球での観測結果とは異なる.オーロラX線の寄与についても議論する. Pitch angle distributions of auroral electrons with energies greater than 40 keV measured by three sounding rockets (S-210JA-20, -21 and S-310JA-2), which were launched from Syowa Station, Antarctica, during moderate disturbances of auroral activity, are presented. The observations were carried out in the altitude range up to 220 km near magnetic midnight. It is shown that pitch angle distributions above 110 km depend upon both energy and altitude. This is in contrast with pitch angle distributions measured at the quiet time or in the northern polar region, where the trapped type distribution with a peak at 90°pitch angle is observed regardless of energy and altitude. A possible influence of auroral X-rays on the observation results is discussed in connection with pitch angle. departmental bulletin paper